Distinct patterns of cytolytic T‐cell activation by different tumour cells revealed by Ca2+ signalling and granule mobilization. Issue 2 (2nd November 2016) - Frick, Melissa; Mouchacca, Pierre; Verdeil, Grégory; Hamon, Yannick; Billaudeau, Cyrille; Buferne, Michel; Fallet, Mathieu; Auphan‐Anezin, Nathalie; Schmitt‐Verhulst, Anne‐Marie; Boyer, Claude
Summary: Cancer‐germline genes in both humans and mice have been shown to encode antigens susceptible to targeting by cytotoxic CD8 T effector cells (CTL). We analysed the ability of CTL to kill different tumour cell lines expressing the same cancer‐germline gene P1A ( Trap1a ). We previously demonstrated that CTL expressing a T‐cell receptor specific for the P1A35–43 peptide associated with H‐2L d, although able to induce regression of P1A‐expressing P815 mastocytoma cells, were much less effective against P1A‐expressing melanoma cells. Here, we analysed parameters of the in vitro interaction between P1A‐specific CTL and mastocytoma or melanoma cells expressing similar levels of the P1A gene and of surface H‐2L d . The mastocytoma cells were more sensitive to cytolysis than the melanoma cells in vitro . Analysis by video‐microscopy of early events required for target cell killing showed that similar patterns of increase in cytoplasmic Ca 2+ concentration ([Ca 2+ ]i) were induced by both types of P1A‐expressing tumour cells. However, the use of CTL expressing a fluorescent granzyme B (GZMB‐Tom) showed a delay in the migration of cytotoxic granules to the tumour interaction site, as well as a partially deficient GZMB‐Tom exocytosis in response to the melanoma cells. Among surface molecules possibly affecting tumour–CTL interactions, the mastocytoma cells were found to express intercellular adhesion molecule‐1, the ligand for LFA‐1, which was not detected on the melanoma cells. Abstract : Video‐microscopy shows an increase in cytosolic Ca 2+ in GZMB‐Tom expressing TCRP1A CTL interacting with a P1A‐positive (but not a P1A‐negative) mastocytoma cell, followed 6 min later by reorientation of the GZMB‐Tom containing granules toward the target cells.